Metal–Organic‐Framework‐Based Photocatalysts Optimized by Spatially Separated Cocatalysts for Overall Water Splitting - Zhang, Jijie; Bai, Tianyu; Huang, Hui; Yu, Mei‐Hui; Fan, Xiaobin; Chang, Ze; Bu, Xian‐He (Advanced materials (Weinheim), 2020)
Efficient charge separation and utilization are critical factors in photocatalysis. Herein, it is demonstrated that the complete spatial separation of oxidation and reduction cocatalysts enhances the efficacy of charge separation and surface reaction. Specifically, a Pt@NH2‐UiO‐66@MnOx (PUM) heterostructured photocatalyst with Pt and MnOx as cocatalysts is designed for the optimization of the NH2‐UiO‐66 photocatalyst. Compared with the pristine NH2‐UiO‐66, Pt@NH2‐UiO‐66 (PU), and NH2‐UiO‐66@MnOx (UM) samples, the PUM sample exhibits the highest hydrogen production activity. As cocatalysts, Pt favors trapping of electrons, while MnOx tends to collect holes. Upon generation from NH2‐UiO‐66, electrons and holes flow inward and outward of the metal–organic framework photocatalyst, accumulating on the corresponding cocatalysts, and then take part in the redox reactions. The PUM photocatalyst greatly prolongs the lifetime of the photogenerated electrons and holes, which favors the electron–hole separation. Furthermore, the PUM sample facilitates overall water splitting in the absence of sacrificial agents, thereby demonstrating its potential as a modification method of MOF‐type semiconductors for the overall water‐splitting reaction. A heterostructured photocatalyst, Pt@NH2‐UiO‐66@MnOx (PUM), is constructed based on the rational optimization of NH2‐UiO‐66 with spatially separated Pt and MnOx nanoparticles as cocatalysts. The optimization results in a long lifetime of the photogenerated electrons and holes in the composite, which can drive overall water splitting in the absence of sacrificial agents.